Hubungan Antara Usia Dengan Preeklampsia Pada Ibu Hamil Di POLI KIA RSUD Kefamenanukabupaten Timor Tengah Utara - Etika Desi Yogi; Hariyanto Hariyanto; Elfrida Sonbay (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2014)
According to data from the North Central Timor Regency Health Office.The number of maternal deaths in 2011 were 12 people from 7000 livebirths. The direct causes of death such as preeclampsia/eclampsia were 5%,50% bleeding, infection was 17%, other causes as many as 28%, the data fromPoly KIA Kefamenanu Hospital in 2011 from 600 pregnant women wereexamined, pregnant women with preeclampsia as many as 35 people. Purposeof this study was to determine the relathionship between age and preeclampsiain pregnant women in the district Kefamenanu Poly KIA Hospital North CentralTimor.Type of research is correlational analytic study with retrospective design.Population in this study were all pregnant women in the district Kefamenanu,Poly KIA Hospital North Central Timor in January to desember 2011, thesampling size were of 35 people, with a total population sampling technique.While research conducted during January to February 2013. Variable studiedwere age (independen), and preeclampsia (dependen). Method of data collectionfor the variables of age and preeklamsia variables using the data on MedicalRecord documentation in Poly KIA, to analyze the relationship between twovariables using a statistical test contingency coefficient.The majority of women aged > 35 years (63,0%), almost entirely (83,0%)mild preeclampsia. Analyze of research data obtained using the Contingencycoefficient test probability(ρ)=0,039≤ ɑ (0,05), which means there is arelationship between age and preeclampsia in pregnant women in the districtkefamenanu Poly KIA Hospital North Central Timor with a low level of closeness(contingency coefficient=0,330).Mother is expected to increase the knowledge that age is one of facto: thatcan causes preeclampsia, so mothers are able to detect early if there is a dangersign/complications.